2019
DOI: 10.3390/ijerph16152771
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium from a Contaminated Soil Using Oxalic Acid, Citric Acid, and Hydrochloric Acid: Dynamics, Mechanisms, and Concomitant Removal of Non-Targeted Metals

Abstract: Soil leaching is an effective remediation technique using agents to leach the target pollutants from the soil. However, the dynamics and mechanisms for leaching of Cr and other non-pollutant metals from Cr-contaminated soils are not yet well understood. Here, column leaching experiments were conducted to determine the effect of hydrochloric acid (HCl), citric acid (CA), and oxalic acid (OX) on the leaching of Cr, as well as of Ca, Mg, Fe, and Mn, from a soil contaminated by a Cr slag heap. Acid leaching decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…E). The detailed characteristics of the two kinds of soil samples were described in our previous studies [7,36]. The soils were first air-dried, then sieved (2 mm).…”
Section: Soil Sample Preparationmentioning
confidence: 99%
“…E). The detailed characteristics of the two kinds of soil samples were described in our previous studies [7,36]. The soils were first air-dried, then sieved (2 mm).…”
Section: Soil Sample Preparationmentioning
confidence: 99%
“…By comparing the experimental data, the bacteria isolated in this study demonstrated a higher chromium reduction efficiency, not only in the initial chromium reduction concentration but also in the chromium reduction time. Furthermore, the leaching method has been mostly used as a strategy for the in situ treatment of polluted soils [53][54][55][56], where the chromate in the soil was continuously eluted by the eluent, typically using the bacteria as the eluent. For example, previous reports demonstrated the use of the bacteria Acidithiobacillus ferrooxidans as the eluent to elute chromium from soil; however, this took as long as 5 weeks [57].…”
Section: The Reducing Ability Of the Isolated Strainsmentioning
confidence: 99%
“…(4) There is no chemical interaction, and the gas is assumed to be ideal gas. (5) It is assumed that the solid, liquid, and gas phases are continuous in unsaturated soil, separately. (6) It is assumed that the migration of liquid and gas do not affect each other.…”
Section: Model Of Heating Fieldmentioning
confidence: 99%
“…A cornucopia of remediation technologies has been developed to treat contaminated soils [5][6][7][8]. Among these technologies, in situ soil thermal remediation holds an important niche role due to its ability to clean pollutants quickly and reliably [9].…”
Section: Introductionmentioning
confidence: 99%